The Influence of Workload, Work Compensation and Work Stress on Nurse Performance at The Bhayangkara Setukpa Lemdikpol Hospital Sukabumi City - Ida (LPPM STIKes Muhammadiyah Ciamis, 2024)
Hospital is a public health service that has the core task of providing guidance and health services to the community by providing comprehensive health services. Nursing services are one of the health service systems in hospitals that have an important role and contribution in improving hospital services. The purpose of the study was to determine whether there was an effect of workload, work compensation and on the performance of nurses at Bhayangkara Setukpa Hospital, Lemdikpol, Sukabumi City. The design used in this study was cross sectional. The instrument used is a questionnaire. The data were analyzed using simple linear regression tests and multiple linear regression. The results showed a simultaneous influence between workload, work compensation and work stress on the performance of implementing nurses at Bhayangkara Setukpa Hospital, Lemdikpol, Sukabumi City. (p=0.000).